CCPR Model: Creation of Characteristics of Modern Learners Through Creative Teaching Method - Sirichokchaitrakool, Sirisukr (Journal of Education Studies, Chulalongkorn University, 2024)
The development of a country is highly competitive globally; the educational system in modern days, therefore, is essentially in need of a change to become more practical and creatively inventive. That can be achieved by changing the educational trend in the system of consumerism to a system that produces creative results from the thinking process, intelligence, or a learning process that includes thinking, inventing, and creating new products instead of only waiting as a consumer until a crisis occurs, as it has done in the past. This academic journal aims at proposing a guideline to create characteristics of a modern learner through a creative teaching method called CCPR Model. This model consists of 1) Critical mindset: an educational plan that focuses on the learners’ ability to analyze, understand, and critically process information. 2) Creative mindset: an educational plan that encourages learners to be inventive, learn new skills, and gain new perspectives. 3) Productive mindset, an educational plan that prepares learners to be self-efficient in productivity by encouraging them to develop new ideas, conduct academic research, and create new products. 4) Responsible mindset: an educational plan that teaches learners to be responsible to themselves, society, and the environment. It introduces them to existing social problems and encourages them to find and engage in solution-oriented activities. This teaching method emphasizes the development of thinking, creativity, and responsibility and the creation of modern learners who can resist the trend of consumerism or can be smart consumers. This important social asset will drive the development of the country and will be an educational tool to truly develop learners.